Switching cycles in Steiner triple systems - Grannell M.J.; Griggs T.S.; Murphy J.P. (Utilitas Mathematica, 1999)
We investigate equivalence classes under the operation of n-cycle switching on isomorphism classes of STS (v)s for v ∈ 7, 9, 13, 15 and n ∈ 4,6,8, 10, 12. We also investigate equivalence classes under the operation of n-cycle switching on realizations of STS(v)s on a fixed base set V for v ∈ 7, 9, 13 and n ∈ 4, 6, 10, and for (v, n) = (15, 12).